Driving the economy through innovation and entrepreneurship emerging agenda for technology management. - Mukhopadhyay, Chiranjit. (Springer)
Modern technologies are central to creation of wealth through business expansion leading to economic development. This is visible in the fast-paced technology-induced economic growth experienced by most countries, especially by rapidly growing economies such as India, China, Brazil, South Korea, among others. Increasing individual scientific contribution, nurturing entrepreneurial talent, promoting innovative competence, strategically prioritizing and investing in technologies and enhancing national economic wealth are some of the important Technology Management goals. Technology Management has emerged as a strategic and knowledge domain of interest to academicians, practitioners, and policy makers across the globe. Technology Management has also evolved into an inter-disciplinary concern which requires national and international collaborations and exchange of insights. Keeping this objective in mind the International Conference on Technology Management is organized by the Department of Management Studies, Indian Institute of Science, Bangalore, a leader in research and education in Technology Management for the last several decades. This conference aims at integrating experiences of academicians, industry leaders, Technology Managers and Innovators towards effective knowledge creation and economic development. The contributions of the present volume are presented at the Conference during 18-20 July 2012. Preface -- E-Governance -- Innovation Management -- Technology and Emerging Markets -- Technology and Supply Chain Management -- Human Resource Management -- Learning and Knowledge Management -- Technology Management -- Technology and Development -- IT Offshoring -- Technology and Innovation -- Technology and Sustainability -- Technology and Market -- Technology Nurturing -- New Product and Services Development.